The use of complementary and alternative medicine (CAM) in children: a telephone-based survey in Korea - Kim Jung-Ha; Nam Chung-Mo; Kim Moo-Young; Lee Duk-Chul (BMC, 2012)
Abstract Background The purpose of this study was to estimate the prevalence and patterns of CAM use in Korean children via a telephone based survey. We also investigated parent satisfaction, a proxy for their child, with CAM therapy and determined the factors affecting satisfaction with CAM use. Methods This study used a landline telephone-based survey to examine a random sample representative of Korean children, aged 0 to 18 years. We assigned and surveyed 2,000 subjects according to age group, gender, and geographical distributions by proportionate quota and systematic sampling of children throughout Korea in 2010. A household of 1,184 with a 18.6% response rate was projected to yield 2,077 completed data. We performed statistical analyses using sampling weight. Results The prevalence of CAM use was 65.3% for the Korean children in our sample population. The most commonly used CAM category was natural products (89.3%). More than half of CAM user's parents reported satisfaction with their therapies (52.7%), but only 29.1% among them had consulted a Western trained doctor regarding the CAM therapies used. Doctor visits were associated with lower satisfaction with CAM use but not with consultation rate with a doctor. Conclusions Our study suggests that CAM is widely used among children in Korea. Medical doctors should actively discuss the use of CAM therapies with their patients and provide information on the safety and efficacy of diverse CAM modalities to guide the choices of CAM users.